The Emergence of COVID-19 and Capital Market Reaction: An Emerging Market Scenario Analysis - ATM Adnan; Md. Mahadi Hasan (Asian Academy of Management Journal of Accounting and Finance, 2021)
This paper investigates the capital market reaction to the first detection of the COVID-19 in Bangladesh. Using a sample of 314 listed firms in Dhaka stock Exchange (DSE), this study employed the event study methodology (ESM) to find any abnormal return (AR) associated to the first COVID-19 detection announcement. Three different return models namely mean-adjusted return, market-adjusted return and market model have been used to calculate the abnormal return and test the statistical significance using both parametric crude dependence and standardised cross-sectional T- test along with non-parametric generalised sign-test and Corrado rank-test. The findings suggest that, despite the perceived weak market efficiency, the announcement of the first COVID-19 detection has a significant negative impact on overall market return on the event day. Additionally, the result exhibits the indifferent market reaction of different industry segments such as manufacturing, service, financial, non-financial, pharmaceuticals and IT and telecommunication sectors. The results would be useful for investors, industrial and financial analysts in accessing volatile systemic risk and building an optimal portfolio to solve the pandemic dilemma effectively.